PENDEKATAN BERBASIS GENRE untuk PENGAJARAN MENGARANG FAKTUAL dalam BAHASA INGGRIS di MADRASAH ALIYAH - Syamsi Hasan (Madania: Jurnal Ilmu-Ilmu Keislaman, 2013)
The ability in exploring ideas until its development sequences has been found many English teachers as frustrated and inadequate outcomes. These fenomena have always been found in the learners’ writing production. It has become a challenging factor that always needs constructive plans in teaching and learning of English. Writing is basically a skill for communicating ideas and feelings in encoded linguistic features to be understood by readers or audiences. However, writing genre needs specific views on how ideas are organized and structured in accordance with the purposes of its writing. For example, a teacher is about to develop a narrative form of genre, he/she has to introduce a model taken from different sources with specific characteristic of a narration. The characteristic may involve generic structure, organization of ideas, and the dominant linguistic features that match with the purpose of writing a narrative text. These all can be understood through which a genre would possibly be approached. This article shows how a genre based approach brings about formulation and consideration on how it should be applied by English teachers at Madarasah Aliyah